Peran Niniak Mamak dalam Penanggulangan Tindak Pidana Perjudian Online Jenis Rolet dan Togel di Kenagarian Simarasok Kecamatan Baso - Hardetta, Hardetta; Yustrisia, Lola; Fitri. Z, Yenny (UNES Law Review, 2023)
One form of crime that occurs in cyberspace is online gambling. Online gambling is considered as a violation of the norms and rules that apply in society. In the Simarasok Village, Baso District, all settlements of cases that occur among the community are followed up by traditional leaders who are called niniak mamak. The purpose of this research is to find out the role and solutions experienced by niniak mamak in the Simarasok Village, Baso District in overcoming criminal acts of online roulette and lottery types. From the results of this research, the role of niniak mamak in the Simarasok Village, Baso District in dealing with online gambling crimes of the roulette and lottery types, namely in the form of preventive measures by providing appeals, supervision, and customary understanding of nephew’s children. The obstacle experienced by niniak mamak in the Simarasok Village, Baso District lies in the process of proving the crime where this crime was committed online through electronic media that has internet access in running the games. The solution to overcome these obstacles is to invite all elements of society who see and find this online gambling activity to immediately report it to niniak mamak.